2021
DOI: 10.3389/fpsyt.2021.676493
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Status Associated With Low Quality of Life in School-Age Children With Neurodevelopmental Disorders During COVID-19 Stay-At-Home Period

Abstract: Background: This study seeks to ascertain how the COVID-19 stay-at-home period has affected the quality of life (QOL) of children with neurodevelopmental disorders (NDDs) who had experienced sleep schedules alteration and clarify what psychological status predicted low QOL in children with and without altered sleep patterns.Materials and Methods: Study participants were 86 children between 8 and 17 years of age (mean age, 11.7 years; 70 boys, 16 girls; mean intellectual quotient, 83.6). QOL was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…13 During the pandemic, sleep disturbances have played a significant role in the deterioration of the quality of life of families of patients with neurodevelopmental disorders. 6,14 Our study found that the child's disturbed sleep stressed the family; however, the stress could not be attributed to this alone. As shown in Table 5, new sleep disorders are stressful for families but pre-pandemic sleep disorders are not, and some families experience stress even without sleep disorders.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…13 During the pandemic, sleep disturbances have played a significant role in the deterioration of the quality of life of families of patients with neurodevelopmental disorders. 6,14 Our study found that the child's disturbed sleep stressed the family; however, the stress could not be attributed to this alone. As shown in Table 5, new sleep disorders are stressful for families but pre-pandemic sleep disorders are not, and some families experience stress even without sleep disorders.…”
Section: Discussionmentioning
confidence: 54%
“…The prevalence of sleep problems during the COVID‐19 pandemic is high, affecting approximately 40% of the general population and healthcare workers 13 . During the pandemic, sleep disturbances have played a significant role in the deterioration of the quality of life of families of patients with neurodevelopmental disorders 6,14 . Our study found that the child's disturbed sleep stressed the family; however, the stress could not be attributed to this alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the available studies vary not only in methodology, but mainly on objectives: one of them compared ADHD and non-ADHD children during the pandemic [12], the second ADHD and non-ADHD before and during the pandemic [33], other the reaction of chronotypes on ADHD children during the pandemic [44], and finally the ADHD childrens' response during the confinement [168]. Therefore, more robust studies are needed to access ADHD children and adolescents' sleep patterns in reaction to the pandemic.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…Longer periods for video games were also reported in this study. Ueda et al reported about half of children, participated in the research, experienced sleep pattern change during the period and its change was predicted by a high level of depression ( 11 ). In Nakachi et al study, change tendency in sleep pattern was also observed in junior and high school students ( 12 ).…”
Section: “Stay At Home” Campaignmentioning
confidence: 99%